Elucidation of antibacterial compounds from inflorescences of banana (Musa balbisiana cv. saba) using liquid chromatography-tandem mass spectrometry - Hoe, Seng Tin; Birdie Scott Padam; Chye, Fook Yee (Bentham Science Publishers, 2020)
Background: Banana by-products are undervalued and their potential remains untapped. They are often composted after the fruits are harvested, reducing the cause of environmental pollutions due to open burning.